2013
DOI: 10.1007/s00408-013-9516-y
|View full text |Cite
|
Sign up to set email alerts
|

Stratification of Malignant Pleural Mesothelioma Prognosis Using Recursive Partitioning Analysis

Abstract: The MPM patients with PS 0-2 and Hb concentration >12.1 or ≤12.1 g dL(-1) without chest pain had favourable prognoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Each of the RPA classes exhibited approximately 10% discrepancy in the 5-year OS (and CSS) compared with neighboring RPA classes. Although risk group definition based on RPA has been widely accepted and adopted to predict the outcomes of several benign and malignant diseases 10 , 14 , 17 19 , it is still not commonly used in the field of breast cancer care. A possible reason is that most surgeons, especially breast cancer surgeons, are not acquainted with this simple method although it requires statistical software to perform the cumbersome calculations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Each of the RPA classes exhibited approximately 10% discrepancy in the 5-year OS (and CSS) compared with neighboring RPA classes. Although risk group definition based on RPA has been widely accepted and adopted to predict the outcomes of several benign and malignant diseases 10 , 14 , 17 19 , it is still not commonly used in the field of breast cancer care. A possible reason is that most surgeons, especially breast cancer surgeons, are not acquainted with this simple method although it requires statistical software to perform the cumbersome calculations.…”
Section: Discussionmentioning
confidence: 99%
“…The visually succinct expression of RPA allows the easy and quick understanding of a complicated prognostic model. 14 Displaying the information in a decision tree model allows readers to understand the importance of specific factors and relationships of factor interaction at a first glance. For example, our results showed that LNR was the most important in this model, followed by ER status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Other research has identified performance status, hemoglobin level, and absence of chest pain as important prognostic features. 33 Following diagnosis of this aggressive life-threatening disease, the information must be sensitively communicated to the patient. Effective communication requires that patients be prepared for the information by having family members or significant others present, tailoring information in a clear, understandable, and honest manner, ensuring privacy and adequate time, offering support, encouraging expression of feelings and concerns, and involving the patient in decision making and the treatment plan.…”
Section: Disease Presentation and Diagnosismentioning
confidence: 99%
“…Diffuse MM (DMM) is an extremely aggressive neoplasia characterized by a high local diffusion rate, with early involvement of the pericardium and the diaphragm, and by high recurrence rates after radical surgical treatment . Median survival time from diagnosis without treatment ranges from 4 to 12 months; nevertheless better results have been reported in patients with favorable biological and clinical parameters, undergoing a multidisciplinary treatment …”
Section: Introductionmentioning
confidence: 99%